A Perspective Studies: Nutritional Interventions and their Impact on Geriatric Health Outcomes - Goyal, Kamal; Mittal, Sanjeev; Gupta, Vikas; Goyal, Ravi Kumar (Indian Journal of Pharmacy Practice)
Age reaching an average life span of human beings is known as old age. There is no exact meaning or definition for old age. During aging, malnutrition is complex and multifactorial. Nutritional interventions have become increasingly important in the field of geriatric healthcare, as the aging population faces a higher risk of malnutrition and related health outcomes. The present review studies aim to synthesize the current evidence on the impact of various nutritional interventions that improves optimal health and well- being of older adults.
Keywords: Geriatric; Nutritional; Intervention; Supplements; Challenges and consideration